Exploration of labeling by near infrared dyes of the polyproline linker for bivalent-type CXCR4 ligands. Issue 21 (1st November 2015) - Nomura, Wataru; Aikawa, Haruo; Taketomi, Shohei; Tanabe, Miho; Mizuguchi, Takaaki; Tamamura, Hirokazu
Graphical abstract: Abstract: We have previously used poly-l -proline linkers for the development of bivalent-type ligands for the chemokine receptor, CXCR4. The bivalent ligands with optimum linkers showed specific binding to CXCR4, suggesting the existence of CXCR4 possibly as a dimer on the cell membrane, and enabled definition of the amount of CXCR4 expressed. This paper reports the synthesis by a copper-catalyzed azide–alkyne cycloaddition reaction as the key reaction, of bivalent CXCR4 ligands with near infrared (NIR) dyes at the terminus or the center of the poly-l -proline linker. Some of the NIR-labeled ligands, which would be valuable probes useful in studies of the behavior of cells expressing CXCR4, have been obtained. The information concerning the effects of the labeling positions of NIR dyes on their binding properties is useful for the design of modified bivalent-type CXCR4 ligands.